PENGARUH KOMPETENSI DAN INDEPENDENSI AUDITOR TERHADAP KUALITAS AUDIT PADA INSPEKTORAT UTAMA BADAN NARKOTIKA NASIONAL - Eva Sugiarti; Nurminingsih; Dinni Agustin (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2023)
This study aims to analyze the effect of auditor competence and independence on audit quality at The Main Inspectorate of the National Narcotics Agency. Population data as many as 42 people were used for the sample of the research object. The data to be obtained in this study uses a questionnaire with a Likert scale in the form of a checklist with statements relating to the research variables along with 5 alternative answers to measure each research variable. The variables studied in this study include Auditor Competence, Auditor Independence, and Audit Quality. The research method uses quantitative methods. The data analysis technique used in this research is quantitative analysis using SEM (Structural Equation Modeling). The results of this study indicate that (1) Auditor Competence has a positive and significant effect on Auditor Independence, (2) Auditor Competence has a positive and significant effect on Audit Quality, and (3) Auditor Independence has a positive and significant effect on Audit Quality.